North-south relations, responsibilities, and agendas in Earth System Governance: Have these changed in the Anthropocene? - Augusto Heras; Joyeeta Gupta (Earth System Governance)
On the G77's 60th anniversary and the 50th anniversary of the Declaration for a New International Economic Order, this paper explores the enduring complexities of North-South relations in development and climate governance. We ask: What is the continuing relevance of the North-South narrative in Earth System Governance and climate change? Utilising North-South literature, this paper examines these relations and responsibilities, emphasising the need to decolonise ESG by challenging entrenched power structures in climate governance. The analysis concludes: (a) the North-South dynamic is a flexible dichotomy reflecting the dominance of powerful nations/actors over the less powerful; (b) recurring patterns of North-South behaviour in controlling forums, agendas, and decisions marginalise Southern perspectives; and (c) such imbalances result in failures to govern ecological and social problems, while the North risks losing control over them. Without a more just approach addressing the North-South dichotomy, we all risk losing a stable and predictable climate.